2012
DOI: 10.1016/j.cct.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of state-mandated insurance coverage on accrual to community cancer clinical trials

Abstract: Thirty-five U.S. states and territories have implemented policies requiring insurers to cover patient care costs in the context of cancer clinical trials; however, evidence of the effectiveness of these policies is limited. This study assesses the impact of state insurance mandates on clinical trial accrual among community-based practices participating in the NCI Community Clinical Oncology Program (CCOP), which enrolls approximately one-third of all NCI cancer trial participants. We analyzed CCOP clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Although somewhat surprising, null findings on state laws are not unprecedented. Prior literature on certain types of state coverage mandates-such as for mental health services (Bao & Sturm, 2004;Chatterji et al, 2015;Pacula & Sturm, 2000) and cancer clinical trials (Chun & Park, 2013;Ellis et al, 2012)-has also concluded null effects. Many of the explanations provided for the lack of effects of these other types of mandates are of limited relevance in the off-label use context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although somewhat surprising, null findings on state laws are not unprecedented. Prior literature on certain types of state coverage mandates-such as for mental health services (Bao & Sturm, 2004;Chatterji et al, 2015;Pacula & Sturm, 2000) and cancer clinical trials (Chun & Park, 2013;Ellis et al, 2012)-has also concluded null effects. Many of the explanations provided for the lack of effects of these other types of mandates are of limited relevance in the off-label use context.…”
Section: Discussionmentioning
confidence: 99%
“…Positive effects on utilization have been found in studies on postpartum delivery mandates (Liu, Dow, & Norton, 2004), fertility treatments (Bitler & Schmidt, 2011;Schmidt, 2007), and breast and colorectal cancer screening (Bitler & Carpenter, 2016;Hamman & Kapinos, 2016). The impact of the laws appears more mixed in research on mental health services utilization (Bao & Sturm, 2004;Chatterji, Decker, & Markowitz, 2015;Pacula & Sturm, 2000) and on cancer clinical trial enrollment (Ellis, Carpenter, Minasian, & Weiner, 2012;Gross, Murthy, Li, Kaluzny, & Krumholz, 2004).…”
mentioning
confidence: 99%
“…1 This component of the legislation is important because insurance denial of routine care costs for trial participation and the length of time to receive a response about coverage from the insurer have both been identified as formidable barriers to adult cancer clinical trial enrollment. [2][3][4][5][6][7][8][9][10] An examination of this self-implementing statute 11 has yet to be reported. Research on the effectiveness of state and federal policies enacted before the ACA and aimed at eliminating the insurance denial barrier yielded variable results regarding the impact on cancer clinical trial participation.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the effectiveness of state and federal policies enacted before the ACA and aimed at eliminating the insurance denial barrier yielded variable results regarding the impact on cancer clinical trial participation. 4,7,[12][13][14][15][16] Before the ACA, federal regulations required trial coverage for Medicare beneficiaries. State statutes were in place to cover patients under other plans but varied in the types of trials, beneficiaries, and payers affected; this created inconsistency in coverage.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons affecting low accrual are varied and complex, but include cost-related hurdles, specifically lack of insurance coverage, especially those with private insurance compared to government-funded insurance [3] , [7] , [8] . Potential denial of coverage was reported as the reason for declining participation for 8–20% and as high as 85% of eligible patients [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%